História do Colégio Agrícola de Uberlândia: da criação a formatura da primeira turma de Técnicos em Agropecuária (1957 - 1972) - Garcia, Daniele da Costa (2011)
This study aims at presenting the results of Research Project History of Colégio Agrícola de Uberlândia: from the school foundation to the first professional degree in the Curso Técnico em Agropecuária (Farm Technician Aprenticeship Program) (1957- 1972). The research was sponsored by Capes, and carried out during the Master s Course in Education Program. The area of concentration is History and Historiography of the Federal University at Uberlândia, having as advisor Professor Doctor Sandra Cristina Fagundes Lima. The main concern is to analyze the history of Colégio Agrícola at Uberlândia, a public technical-professional teaching high school, studying from its creation and foundation to the first course degree in Técnicos em Agropecuária , (Farm Technician Aprenticeship Program) from 1957-1972. The period of study is from the beginning of the school construction to the professional degree awarded to the first group of students, once the construction took twelve years, until 1969. In order to analyze the first group of students the following categories were employed: school architecture, time and space, knowledge and pedagogical practices, and teachers/students profiles. Former students were investigated to understand if their formation has reached the expectations and objectives of the school. The documents collected and used as base for the research analysis are stored in the Public Archive at Uberlândia (ArPU), in the Association of Commerce and Industry at Uberlândia (Aciub), and in the school archive as well. From the press we investigated the newspapers Correio de Uberlândia , O Triângulo and 7 Dias ; records of the City Council were used once they are sources that, through the alderman speeches, represent the politics context of the time. Fourteen former students of the first group were interviewed, based on oral history. A bibliographical study was conducted based on pictures, enrollment forms, and students and teachers personal data found in the school archive. The sources allowed the analysis and understanding the events and educational discussions on a national/regional level. The results were compared to the specialist literature according to the Brazilian reality. We have carried out a descriptive study of the institution, and developed a dialogue based on history and theory. Our intention was also to look for inter-relations with the Brazilian education issues, mainly on what refers to farm teaching. The results show the importance of the foundation of Colégio Agrícola at Uberlândia once it has contributed to modernize the primary sector both in the city and countryside.